Internal damage growth in quasi-brittle fibre-reinforced cementitious materials under cyclic compressive loading - Sagar, R. Vidya; Basu, Dibya Jyoti; Reddy, K.V. Suhas; Prathap, Y.; Bhuvaneswari, G.; Keerthi, P. Sai (Journal of Structural Engineering, 2024)
This article reports a comparison between the internal damage growth in cementitious materials without fibres and with fibres subjected to elevated amplitude cyclic compressive loading. The damage progression was assessed using ultrasonic testing method and Acoustic Emission (AE) testing. The intricate fracture mechanism in the test specimens causes rise to a higher harmonic generation, which was used as an indicator to the internal damage. The decrement in wave peak amplitude with higher harmonic generation may be regarded as a ‘internal damge growth’ in the deformable solid. The complexity in the fracture mechanism in fibrous cementitious matrix influenced the heterogeneity of the specimen, which is reflected by the steep decrement in the slope of the line plotted using normalized higher harmonic ratio and load. It was observed that the ‘magnitude of the total damage’ developed in plain concrete at the last loading phase was relatively lower than brass coated steel fibre reinforced concrete. This was supported by the damage parameter based on generated AE, where final failure of the specimens preceded an AE avalanche. Therefore, the utilization of a combination of nondestructive testing techniques such as AE and nonlinear ultrasonic testing can offer a more comprehensive understanding of the progression of damage in quasi-brittle cementitious materials.